Determinants of International Fragmentation of Production in the European Union - Götz Zeddies (Leibniz-Institut für Wirtschaftsforschung Halle (IWH), 2007)
The last decades were characterized by large increases in world trade, not only in absolute terms, but also in relation to world GDP. This was in large parts caused by increasing exchanges of parts and components between countries as a consequence of international fragmentation of production. Apparently, greater competition especially from the Newly Industrializing and Post-Communist Economies prompted firms in 'high-wage' countries to exploit international factor price differences in order to increase their international competitiveness. However, theory predicts that, beside factor price differences, vertical disintegration of production should be driven by a multitude of additional factors. Against this background, the present paper reveals empirical evidence on parts and components trade as an indicator for international fragmentation of production in the European Union. On the basis of a panel data approach, the main explanatory factors for international fragmentation of production are determined. The results show that, although their influence can not be neglected, factor price differences are only one out of many causes for shifting production to or sourcing components from foreign countries. – – Die zurückliegenden Jahrzehnte waren weltweit durch eine erhebliche Ausweitung der internationalen Handelsströme, nicht nur absolut, sondern auch in Relation zum Welt-BIP, gekennzeichnet. Dies ist zu einem Großteil auf den zunehmenden bilateralen Handel mit Vor- und Zwischenprodukten als Folge der internationalen Fragmentierung der Produktion zurückzuführen. Offensichtlich hat der im Laufe der Zeit zunehmende internationale Wettbewerbsdruck, insbesondere seitens der südostasiatischen und der mittel- und osteuropäischen Länder, die Unternehmen in Hochlohnländern veranlasst, internationale Unterschiede in den Faktorpreisen, vor allem in den Arbeitskosten, zur Steigerung ihrer preislichen Wettbewerbsfähigkeit auszunutzen. Allerdings wird die Verlagerung von Teilelementen der Wertschöpfungsketten ins Ausland aus theoretischer Sicht, neben Faktorpreisunterschieden, von einer Vielzahl weiterer Faktoren bestimmt. Vor diesem Hintergrund veranschaulicht der vorliegende Artikel auf der Basis bilateraler Daten zum Außenhandel mit Vor- und Zwischenprodukten das Ausmaß der internationalen Fragmentierung der Produktion in der Europäischen Union. Zudem werden im Rahmen einer Paneldaten-Analyse die wesentlichen erklärenden Größen der vertikalen Aufspaltung von Wertschöpfungsketten bestimmt. Die Ergebnisse zeigen, dass internationale Unterschiede in den Arbeitskosten zwar ein wesentlicher, aber dennoch nur ein erklärender Faktor unter vielen sind.
urn:nbn:de:gbv:3:2-6293
Keywords: F14; F23; L23; 330; economic integration; international fragmentation of production; Internationale Arbeitsteilung; Komparativer Kostenvorteil; Lieferanten-Kunden-Beziehung; Outsourcing; Auslandsproduktion; Vorprodukt; EU-Staaten